FORMULATION AND EVALUATION OF CONTROLLED RELEASE MUCOADHESSIVE MATRIX TABLETS OF LEVAMISOLE: ASSEMENT OF PURIFIED FRUIT PULP POLYSACCHARIDE ISOLATED FROM AEGLE MARMELOS AS MUCOADHESIVE EXCIPIENT - Chakraborty, Jashabir; Dash, Suvakanta; Das, Biswajit (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Mucoadhesive tablets have been developed for Levamisole using natural mucoadhesive material such as purified polysaccharide isolated from the ripe fruit pulp of Aegle marmelos. Lin (AMPS) and evaluate in-vitro, in-vivo mucoadhesive properties to assess its efficacy as mucoadhesive agent. Method: The tablets were formulated with AMPS in different concentration employing wet granulation method. Pre-compression tests, tablet parametric tests, swelling index and In-vitro drug release kinetics were performed. Optimization of formulation was done on the basis of controlled and maximum amount of drug release with respect to time. In-vitro, ex-vivo evaluation of mucoadhesion was performed with all prepared formulation but in-vivo evaluation was done by X-ray with optimized formulation (F40) in rabbit. Stability studies were carried out according to ICH guide line with optimized formulation. Results: The tensile strength, mucoadhesive strength and swelling index increase as the natural polymer concentration increase. The release Kinetics and mechanism of release were calculated by fitting in-vitro release data in various models demonstrating that release. In vitro drug release of the optimized batch (F40) was best fitted and explained by Korsemeyer–Peppas and zero order drug release; (Rp=0.9891) and (Ro=0.9842) showed highest linearity and n value 0.97>0.5<1. Hence, pattern of drug release by non-Fickian erosion controlled release. Studies of the optimized formulation demonstrate no significant change in the tensile strength, mucoadhesive strength and drug assay. Conclusion: These research outcomes clearly specify the potential of the AMPS to be used as mucoadhesive, release retardent natural material in tablet formulation Keywords: Polysaccharide, Acrylamidopropylmethane sulfonic acid, Aegle marmelos, Levamisole, Mucoadhessive.